2019
DOI: 10.25130/j.v24i5.858
|View full text |Cite
|
Sign up to set email alerts
|

The effect of L-Arginine of treatment for infertile men on semen parameters

Abstract: The aim of the study is to determine the effect of oral supplement of L-Arginine on semen parameters as a treatment for infertile men. Patients and methods: The study conducted on 15 infertile men at infertility clinic in SalahadDin general hospital and private clinics and laboratories in Tikrit city from beginning of March to the end of July 2018. Infertility is a common clinical problem affecting 13-15% of couples worldwide. The prevalence varies throughout developed and undeveloped countries, being higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…But semen analysis before and after treatment with levo-carnitine showed Manssor et al observed a significant increase in sperm count in infertile men treated with (L-carnitine, and the mean and standard deviation of increment in sperm count after four months of treatment (51±4.78), which is similar to our study. 27 We also found that the comparison of semen analysis of both groups reflected statistically significant differences (p<0.05) in semen motility (36.58±5.16 vs 14.36±1.19).…”
Section: Discussionsupporting
confidence: 58%
“…But semen analysis before and after treatment with levo-carnitine showed Manssor et al observed a significant increase in sperm count in infertile men treated with (L-carnitine, and the mean and standard deviation of increment in sperm count after four months of treatment (51±4.78), which is similar to our study. 27 We also found that the comparison of semen analysis of both groups reflected statistically significant differences (p<0.05) in semen motility (36.58±5.16 vs 14.36±1.19).…”
Section: Discussionsupporting
confidence: 58%